(untitled) (Bulletin of the International Association for Paleodontology, 2025)
Accurate age estimation in children is crucial in various justice-related contexts, including adoption, asylum claims, and immigration cases. Additionally, dental age estimation plays a key role in treatment planning within pediatric dentistry and orthodontics. This study aimed to assess the applicability of two widely used dental age estimation methods, Demirjian and Nolla, for children aged 6 to 15 years in Surabaya, Indonesia. A total of 200 panoramic radiographs from the Dental Hospital, Universitas Airlangga were analyzed to compare chronological age (CA) and estimated dental age (DA). The results revealed significant differences between CA and DA when using the Demirjian method for males (p < 0.05) and the Nolla method for both sexes (p < 0.05). However, no statistically significant differences were observed for females using the Demirjian method. The Demirjian method demonstrated greater accuracy, with the lowest mean absolute error (MAE) of 0.92 years for males and 0.82 years for females, compared to the Nolla method, which showed an MAE of 1.10 years for males and 0.87 years for females. These findings suggest that the Demirjian method is more reliable, particularly for estimating the dental age of females in the Surabaya population. Additionally, the Demirjian method showed higher accuracy in younger children (ages 6–10 years), while the Nolla method performed better in older children (ages 11–15 years).